A Histologically Complete Response to Immunotherapy Using Pembrolizumab in a Patient with Giant Cell Carcinoma of the Lung: An Additional Report and Literature Review. (15th October 2019) - Kakimoto, Tomoo; Sasaki, Mamoru; Yamamoto, Tatsuya; Iwamaru, Arifumi; Ogata, Kentaro; Lee, Ko; Nakayama, Shingo; Minematsu, Naoto
Abstract : We previously reported a case of giant cell carcinoma in the lung, in which the use of antiprogrammed death 1 (PD-1) immunotherapy resulted in substantial tumor reduction. In the present study, we describe an additional clinical course. A 69-year-old woman was diagnosed with giant cell carcinoma of the lung in clinical stage IVB (T2bN0M1c, BRA). The tumor expressed programmed death ligand 1 (PD-L1) in a high proportion. The patient received stereotactic radiotherapy for two sites of small brain metastases, followed by immunotherapy using anti-PD-1 antibodies (pembrolizumab). The treatment exerted a substantial tumor reduction through four cycles. However, treatment was withdrawn due to renal dysfunction. The primary lung tumor continued to regress for an additional four months without any further therapy, resulting in a clinical stage of T1aN0M0. Salvage thoracic surgery was then performed to remove the tumor residue in the lung. Microscopic examination of the sample revealed no residual cancer. The patient was free from recurrence at 16 months post surgery. We then comprehensively reviewed lung sarcomatoid carcinoma cases in the literature, in which anti-PD-1 antibodies were implemented. The current literature and our own findings suggest sarcomatoid carcinomas express high levels of tumoral PD-L1 and can be effectively treated with anti-PD-1 antibodies.